PRECEDENTIAL NAMES IN ADVERTISING - Amankevičiūtė, Simona (Verbum, 2015)
The subject of this article is dispersion of precedential names in advertising. To evaluate the qualities of precedential name actualization in ads, this paper analyses examples of advertisement with actualized precedential personalities. One of the elements of precedential phenomena space, precedential name (PN) is an individual name which has a close relation to a well known text or situation. A PN represents a sign of its kind, in usage PN appeals to its differential attributes. This article also reviews obscene cases of attribution in ads, defines and evaluates concepts of social stigma and meta-violence, and analyses cases of practical actualisation of positive and negative sign personalities in ads. Referring to the theory of the exploitation of an image (Baudrillard), this article presupposes that ads actualising a highly negative PN are considered as obscene and intentionally shocking. Referring to the concept of associated stigma (Goffman), the article considers the influence of using a negative sign PN in an ad on the product image. Theoretically, each example of PN actualisation in an ad is to be considered as obscene (the choice of PN as a subject is always possible, but not necessary), but evaluation depends on a specific example. The choice of PN to be used in an ad is a delicate matter: personality with negative invariant may cause public resentment and impair the product image; actualisation of personality with positive invariant can also cause public resentment when a respected person is depicted as a stereotypical depersonalized caricature. Historical figures are used in precedential ads more frequently than live people, with an exception of politicians, who are depicted disrespectfully and incorrectly. A PN of a negative sign are the most used in ads: such actualisation may not cause a direct uproar, but a product will be associated with negative attributes of the particular personality. Evaluating the competence of an addresser, it can be stated that such elements as lack of any logical relation between ads’ subject and object, wrong choice of ads’ character (PN) and its trivialisation, and undervaluation of addressee’s competence to recognise a PN demonstrates advertisers’ lack of competence to actualise a PN.